Beyond presentation effects: Understanding the role of language by hand in the holistic rating of young students’ writing in Grade 4 - Roessingh, Hetty; Nordstokke, David; Colp, Mitch (Alberta Journal of Educational Research, 2019)
The goal of this study is to glean research insights into the role of handwriting on the holistic rating of young students’ expository writing samples in Grade 4. We focus on the interaction of compositional fluency—the total number of words (TNW) generated, the quality of the handwriting, the style of handwriting, and the holistic rating of writing outcomes on an expository prompt. We observed a relationship between fluency, quality of handwriting, and holistic rating of the writing samples, suggesting the need for sustained instructional attention to handwriting to achieve academic literacy in Grade 4. More than merely “looking pretty on the page,” the quality of the handwriting is reflective of the neuro-motor control required to develop fluency or productivity for the academic requirements of upper elementary writing tasks. Samples of Grade 4 handwriting are provided to illustrate and support the quantitative findings of this inquiry. L’objectif de cette étude est d’obtenir un aperçu du rôle de l’écriture dans l’évaluation globale de récits par de jeunes élèves en 4e année. Nous nous penchons sur la fluidité du texte—le nombre total de mots rédigés, la qualité de l’écriture, le style de l’écriture et l’évaluation globale du récit sur un sujet donné. Nous avons noté un lien entre la fluidité, la qualité de l’écriture et l’évaluation globale des récits, ce qui suggère le besoin d’une attention pédagogique soutenue à l’écriture, de sorte à ce que les élèves atteignent une littératie académique en 4e année. La valeur d’une belle écriture dépasse le sens esthétique : la qualité de l’écriture reflète la régulation neuromotrice nécessaire au développement de la fluidité et au rendement qu’exigent les travaux de rédaction dans les années scolaires subséquentes. Des échantillons de rédactions par les élèves en 4e année viennent illustrer et appuyer nos résultats quantitatifs. Mots clés : littératie écrite; écriture; fluidité textuelle; qualité du récit